Two Painted Wooden StelaeFrom The Cairo Museum (Je 18651 & Je 4886) - Zakareya R. ABDELMAGUID (Fayoum University, 2015)
This article is a publication of two wooden funerary stelae from the Egyptian Museum in Cairo, bearing the inventory numbers JE 18651 and JE 4886 (SR nos. A 9906 and A 9403). The stelae have never been fully published. The owners are a certain Hor-nakht, son of Ankh-Hor, and overseer of the God's Wife Aqr, named Dd-BAstet-jnk-sy, son of the vizier Jry. Both stelae are coming from Thebes and they are dating from the Late Period (Dynasties. 25/26). The inscriptions contain some interesting features in the spellings of the epithets and offering formulae. The two stelae are part of a large number of very interesting Late Period wooden funerary stelae in the magnificent collection of antiquities in the Cairo Museum. It is noteworthy that the owners of these stelae are mostly persons attached to the cults of the gods Month and/or Amun. The stelae vary in size from a few centimetres to nearly one meter. They also vary in the quality of workmanship; some being carefully inscribed and artistically decorated, while others are quite poor. With some exceptions, the larger stelae are the best in this respect. One may wondered why wood should have been used as a material for these stelae, and the first idea that comes to mind is reason of economy. But a close study of the material in hand seems to dispute that reason. For one thing, the better-class wooden stelae cannot have been cheap. They have evidently been decorated by first-class artists, and some of them are even embellished with gold. Moreover, many of them belonged to persons of high social standing. Perhaps the portability of wood against the heaviness of stone determined the use of the former material. In addition, these offer an interesting view on aspects of the religion of this Period, particularly on the identification of the forms of Horakhty with Sokar-Osiris. It also is noteworthy that all stelae seem to originate from Thebes and its neighbourhood, namely from the Ramesseum, Deir el-Bahari, Sheikh Abd El-Qurnah, and MedinetHabu. Both stelae were discovered in Sheikh Abdel Qurnah, the first in 1862, and the second in 1859.